2017
DOI: 10.1016/j.jiph.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Public response to MERS-CoV in the Middle East: iPhone survey in six countries

Abstract: Gulf Cooperation Council (GCC) countries bear the heaviest brunt of MERS-CoV. This study aims to compare public awareness and practice around MERS-CoV across GCC countries. A cross-sectional survey was conducted using the Gulf Indicators (GI) smartphone app among people in the six GCC countries, namely Saudi Arabia, Kuwait, the United Arab Emirates, Qatar, Bahrain, and Oman. A total of 1812 participants recruited. All were aware of MERS-CoV, yet the perception and practice around MERS-CoV varied widely between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 30 publications
3
42
1
2
Order By: Relevance
“…271-2.380). This may be attributed to several factors: (1) access to healthcare facilities could be an issue for non-healthcare workers, and thus warrants further investigation, (2) the symptoms of MERS may not be clearly obvious to non-healthcare workers, as there are gaps in knowledge about the virus and symptoms in this group (Assiri et al, 2013b;Alqahtani et al, 2017). An interventional study may target the level of knowledge in the non-healthcare worker group to improve their understanding of the virus and symptoms, and the importance of the early notification of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…271-2.380). This may be attributed to several factors: (1) access to healthcare facilities could be an issue for non-healthcare workers, and thus warrants further investigation, (2) the symptoms of MERS may not be clearly obvious to non-healthcare workers, as there are gaps in knowledge about the virus and symptoms in this group (Assiri et al, 2013b;Alqahtani et al, 2017). An interventional study may target the level of knowledge in the non-healthcare worker group to improve their understanding of the virus and symptoms, and the importance of the early notification of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to better universal health coverage, and flexibility to choose health care professionals compared to Saudi Arabia, where the government has more restrictions and involvement in healthcare decisions [56,57]. From the beginning of the outbreak, South Korean patients who were MERS-positive sought and embraced medical attention much faster than did Saudi Arabian patients [58]. However, this brings about the previously discussed problem of visiting a variety of healthcare environments prior to diagnosis, exacerbating spread.…”
Section: Aspect 1 -Public Information and Quarantine/isolation Practicesmentioning
confidence: 99%
“…While Saudi Arabian officials did put in place a Rapid Response Team (RRT) to combat the outbreak, a 2017 study found that, even several years after implementation, many interviewed Health Care Workers, nurses, and other hospital support staff were not fully compliant with these guidelines, putting themselves and patients at risk for MERS-CoV infections [58]. The general feeling of Saudi Arabian workers and citizens was largely that MERS was not a substantial problem, and holes in primary care practices in addition to spread by dromedaries and humans alike in the population contributed to the continuing epidemic in the Saudi Arabian region.…”
Section: Aspect 2 -Personal and Cultural Belief Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This incident acted as epicentre spreading first in neighbouring countries then globally. ( Alqahtani et al, 2017 ), alike Ebola or swine flu it became an alarming threat to global health security. The Middle East respiratory syndrome (MERS) is acute respiratory viral infection caused by novel extremely pathogenic coronavirus ( Ahmadzadeh et al, 2020 ; Alosaimi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%